2022
DOI: 10.3389/fpsyg.2022.721219
|View full text |Cite
|
Sign up to set email alerts
|

The Innovation of Entrepreneurship Education for Intangible Cultural Heritage Inheritance From the Perspective of Entrepreneurial Psychology

Abstract: The purpose is to help college students start their own businesses and protect and develop China’s intangible cultural heritage. The entrepreneurship of college students in the field of intangible culture is studied from the perspective of entrepreneurial psychology. First, the related characteristics, main content, and research status of college entrepreneurship education are described in detail. Entrepreneurial psychology is divided into entrepreneurial cognition, entrepreneurial emotion and entrepreneurial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…An increasing number of universities offer ICH design courses to develop the ICH design skills of students. Recent years have witnessed numerous studies on ICH design education, many of which have focused on ICH transmission and talent development [27][28][29].…”
Section: Current Issues About Teaching Ich Coursesmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of universities offer ICH design courses to develop the ICH design skills of students. Recent years have witnessed numerous studies on ICH design education, many of which have focused on ICH transmission and talent development [27][28][29].…”
Section: Current Issues About Teaching Ich Coursesmentioning
confidence: 99%
“…Moreover, students are often from arts/design or related departments, which makes them less able to translate their ideas into interactive design works. Reportedly, teaching methods in arts and design education sometimes have a detrimental effect on the creativity of students [28]. Consequently, students in conventional ICH design courses often perform poorly [30].…”
Section: Current Issues About Teaching Ich Coursesmentioning
confidence: 99%
“…According to the field survey conducted by the renowned sociologist Fei Xiaotong in Shanxi rural areas in the 1930s, the situation of cave dwelling housing in major rural areas at that time was as follows: From the data in Table 2, it can be observed that despite the accelerated process of urbanization in modern times, cave dwelling housing still dominates in Shanxi rural areas, with a large number of households and widespread distribution [3]. At the same time, there have been changes in the decoration, furnishings, and facilities of cave dwellings, moving towards a more simple and practical direction.…”
Section: Characteristics Of Shanxi Cave Dwellings In Modern Timesmentioning
confidence: 99%
“…As noted by Tavares, Alves, and Vásquez [16], ICH encompasses the tools, objects, artifacts, and cultural spaces that communities, groups, and individuals recognize as integral to their cultural heritage. The transmission of ICH is a people-centered cultural dissemination that shapes one's morality, character, sentiment, will, ideals, beliefs, values, humanities, artistic taste, thinking mode, wisdom, and practical ability [17,18]. Therefore, it is necessary to further study the current status of ICH and its recreation through the market [17,19].…”
Section: Introductionmentioning
confidence: 99%